Multipass validation with XSD and schematron part 2 using schematron rules to enforce good W3C schema design. - Schwarzenbach, Eric J.
In Part 1 of this article (XML-J, Volume 4, issue 7) we outlined why a development group might consider alternative validation schemes. An example from our experience is applying work group rules to the process of XSD design. We said rules could take the form of a Schematron schema that would be applied when a developer validates an XSD against the schema for XSD. In our past work, a need existed for a productive way to put the alternative into play without losing familiar tools or disrupting current development patterns. For that reason we developed a simple multipass validation framework using XMLSPY's Scripting Environment. In this installment, we walk you through the scripting that remains to be set up and then look at how our framework can be a productive tool for your real world use.